The Human SCN9AR185H Point Mutation Induces Pain Hypersensitivity and Spontaneous Pain in Mice - Xue, Yaping; Kremer, Mélanie; Muniz Moreno, Maria del Mar; Chidiac, Celeste; Lorentz, Romain; Birling, Marie-Christine; Barrot, Michel; Herault, Yann; Gaveriaux-Ruff, Claire (Frontiers in Molecular Neuroscience, 2022)
The voltage-gated sodium channel Nav1.7 is encoded by SCN9A gene and plays a critical role in pain sensitivity. Several SCN9A gain-of-function (GOF) mutations have been found in patients with small fiber neuropathy (SFN) having chronic pain, including the R185H mutation. However, for most of these variants, their involvement in pain phenotype still needs to be experimentally elucidated. In order to delineate the impact of R185H mutation on pain sensitivity, we have established the Scn9aR185H mutant mouse model using the CRISPR/Cas9 technology. The Scn9aR185H mutant mice show no cellular alteration in the dorsal root ganglia (DRG) containing cell bodies of sensory neurons and no alteration of growth or global health state. Heterozygous and homozygous animals of both sexes were investigated for pain sensitivity. The mutant mice were more sensitive than the wild-type mice in the tail flick and hot plate tests, acetone, and von Frey tests for sensitivity to heat, cold, and touch, respectively, although with sexual dimorphic effects. The newly developed bioinformatic pipeline, Gdaphen is based on general linear model (GLM) and random forest (RF) classifiers as well as a multifactor analysis of mixed data and shows the qualitative and quantitative variables contributing the most to the pain phenotype. Using Gdaphen, tail flick, Hargreaves, hot plate, acetone, cold plate, and von Frey tests, sex and genotype were found to be contributing most to the pain phenotype. Importantly, the mutant animals displayed spontaneous pain as assessed in the conditioned place preference (CPP) assay. Altogether, our results indicate that Scn9aR185H mice show a pain phenotype, suggesting that the SCN9AR185H mutation identified in patients with SFN having chronic pain contributes to their symptoms. Therefore, we provide genetic evidence for the fact that this mutation in Nav1.7 channel plays an important role in nociception and in the pain experienced by patients with SFN who have this mutation. These findings should aid in exploring further pain treatments based on the Nav1.7 channel.